Vanadyl Sulfate Effects on Systemic Profiles of Metabolic Syndrome in Old Rats with Fructose-Induced Obesity - Diego Ortega-Pacheco; María Marcela Jiménez-Pérez; Jeanet Serafín-López; Juan Gabriel Juárez-Rojas; Arturo Ruiz-García; Ursino Pacheco-García (International Journal of Endocrinology)
Background. Currently, energy obtained from hypercaloric diets has been part of the obesity and type 2 diabetes mellitus (T2DM) epidemics from childhood to old age. Treatment alternatives have been sought from plants, minerals, and trace elements with metabolic effects. Vanadyl sulfate (VS) has been investigated as a hypoglycemic compound in animal and human studies showing effective insulin-mimetic properties. This characteristic encompasses several molecules that have beneficial pleiotropic effects. The aim was to determine the antiobesity, hypoglycemic, and hypolipidemic effects of VS on fructose-induced metabolic syndrome in aged rats. Material and Methods. Five groups of male Wistar rats were made, each with six rats: two groups with normal diet (ND) and three with high-fructose diet (HFD). The first ND group was treated with saline solution (SS), the second with VS; treatment for HFD groups was in the first group with SS, second with VS, and third with metformin. Weight, body mass index (BMI), blood glucose, and lipidic profile were measured; water, food, fructose and energy consumption were also determined. All parameters were compared among groups. Results and Discussion. Although obese rats treated with VS presented anorexia, oligodipsia, and a marked weight loss in the first two weeks. They recovered food and water intake in the third week with a slow recovery of some weight weeks later. VS normalized blood glucose level and decreased triglyceride and insulin levels in obese rats. These results suggest that vanadyl sulfate shows antiobesity, hypoglycemic, and hypolipidemic properties in old obese rats and could be useful as an alternative, additional, and potent preventive treatment for obesity and T2DM control in elderly obese and poorly controlled diabetic patients. Conclusion. VS could play an important role in the treatment of metabolic syndrome, contributing to a decrease in obesity and T2DM, through different ways, such as euglycemia, satiety, weight loss, and lipid profile optimization, among others. However, more research is needed to confirm this suggestion.